Comparing The Effectiveness Of Traditional And Flex Blended Learning Approach On Student Academic Achievement - Syeda Saba Kazmi; Dr. Sajid Rehman; Prof. Dr. Muhammad Naeemullah; Dr. Muhammad Jamil Bajwa; Dr. Rabia Tabassum (Kurdish Studies, 2024)
This study investigated the effectiveness of flex blended learning compared to traditional classroom instruction in teaching Educational Statistics to B.Ed. (Bachelor of Education) (1.5) students at the Federal College of Education, Islamabad. Forty students were randomly divided into experimental and control groups based on pre-test scores. The experimental group received instruction using a flex blended approach, which provided students with greater flexibility in terms of time, place, and pace of learning. In contrast, the control group followed a traditional lecture-based format. Both groups studied the same topics over three weeks. Pre-test and post-test data was collected and analyzed using t-tests. The results revealed a significant difference in academic performance between the two groups, with the flex blended learning group demonstrating superior outcomes. The study suggests that the flex blended approach can be a valuable tool for enhancing student achievement in Educational Statistics and other social sciences subjects.